Consumerism Behaviour of Indonesian Consumer: The Role of Self-Sufficiency and Information-Seeking - Megawati Simanjuntak; Rahma Indina Harbani (Jurnal Manajemen dan Organisasi, 2022)
This study aimed to analyze the influence of information-seeking, knowledge, and self-sufficiency on Indonesian consumerism behaviour. There were 2100 data determined by using systematic random sampling. Data analyses applied Structural Equation Modeling using LISREL 8.7. The results confirmed that information-seeking significantly influence consumers’ knowledge. However, consumers’ self-sufficiency did not considerably affect information-seeking. It also revealed a significant positive effect of information-seeking and self-sufficiency toward consumerism behaviour, but no significant impact between consumers’ knowledge and consumerism behaviour. The government and consumer protection institutions need to be more intensive in conducting socialization to increase consumer knowledge and consumerism behaviour.